Health Effect of Low-Dose-Rate Irradiation with Cumulative Threshold Dose: A Promising Area to Explore in Nuclear Emergency and Environmental Contamination - Feng Ru Tang (Cells)
Humans live in an environment in which they are constantly exposed to meagre dose rates of radiation [...]